Penerapan Metode CART Dalam Klasifikasi Jurusan Siswa Baru - Destia Arini Hairunnisa; Cucu Suhery; Rahmi Hidayati (Journal of Computer System and Informatics (JoSYC), 2023)
SMK Negeri 3 Pontianak is one of the vocational education schools in Pontianak City. Every new academic year SMK Negeri 3 Pontianak accepts around 320 new students. The large number of prospective new students makes the majoring process carried out by the school become less effective and takes a long time to determine majors for new students. With a system that can classify new student majors, it helps in the process of determining student majors. This study uses the Classification and Regression Trees (CART) algorithm for the classification process in determining majors for new students. The assessment indicators used for classification consist of interest, MTK (US) school exam scores, school exam IPA scores, school exam Indonesian language scores, math report cards, science report cards, social science report cards, Indonesian language report cards, and English report cards. Classification of majors at SMK 3 Pontianak consists of accounting, office, marketing, and hospitality majors. The amount of data used is 320 data which is divided into 224 training data and 96 test data. The CART algorithm generates decision trees, rules, and new student majors that have been classified. Based on the test results using the confusion matrix, the system accuracy results are 84.38%.